Commentary: The State That Signed the Contract Felled a City-One Voice at the Intersection of Public War and Private Profit - Peters, Wim C. (Social justice, 2007)
Failing to increase the size of active duty U.S. military forces since the September 11, 2001, terrorist attacks has had tragic consequences. In 2008, private contractors outnumber active duty U.S. troops on the ground in the Iraq war, and, despite increasing reports of their brutal conduct, they are free from systemic or effective control. By contracting out the conduct of the war, state agencies have been allowed to contract out a superior's potential for criminal liability in the event of war crimes being committed by subordinates. Given that the power to start a war lies with the head of state, the head of state should also be accountable for all of war's results.